Preservice Teachers’ Attitudes Toward Inclusive Education Policy in the United States - Ajuwon, Paul M.; Laman, Effie; Earle, John Christopher (Journal of the American Academy of Special Education Professionals, 2014)
The attitudes of 224 preservice teachers from eight universities in the United States were measured to determine if participants’ sentiments, attitudes, and concerns about inclusion can be positively affected through a single course, i.e., using pre and post data gathered with one instrument. There were significant differences between a number of institutions’ pre and post attitudes, sentiments, and concerns that likely stem from variations in the curricula and timing of the individual courses. Key demographic variables appeared to significantly account for the wide range of responses in sentiments, attitudes and concerns in both the pre- and post-training surveys. The percent variance explained by each demographic variable indicates the most influential factors were the level of confidence in one’s ability to teach in an inclusive setting, the candidates’ level of interactions with persons with a disability, previous training related to working with persons with a disability, knowledge of legislation and policy regarding inclusion, and in their previous experience teaching students with disabilities. Legislation and policy can easily be taught in inclusive programs, but important factors relating to confidence and experience with persons with a disability require "real world", structured opportunities to promote inclusion.